2017
DOI: 10.1557/jmr.2017.355
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced materials performance of Al/Ti/Al laminate sheets subjected to cryogenic roll bonding

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…When the asymmetric rolling reduction ratio reaches 70%, ultrafine-grained microstructure can be obtained. Cryorolling [26][27][28][29] has been used to produce ultrafine-grained light metals such as aluminium and copper sheets.…”
Section: Discussionmentioning
confidence: 99%
“…When the asymmetric rolling reduction ratio reaches 70%, ultrafine-grained microstructure can be obtained. Cryorolling [26][27][28][29] has been used to produce ultrafine-grained light metals such as aluminium and copper sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Laminated metal composites are composed of alternating layers of metals or alloys, bonding together at their interface, which have gained extensive attention because of their advantages such as improved fracture toughness, impact behavior, corrosion, wear, and damping capacity, [1,2] and have many applications in industrial sectors such as aerospace, automotive, and household applications. [3,4] To fabricate laminated metal composites, researchers have developed many methods such as hot roll bonding, [5,6] cold roll bonding, [7,8] cryogenic roll bonding, [9] accumulative roll bonding, [10,11] cross-accumulative roll bonding, [12,13] and explosive welding. [14,15] Roll bonding is the most widely used method to process all kinds of metallic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive researches on the mechanical properties and the microstructures of the Al/Cu, [23][24][25] Al/Ni, [26] Al/Ti, [9] and Al/Mg [27] composites have been conducted. Sandwich-like Cu/Al/Cu composites have several reasons for their wide applications such as their high conductivity, low density, and price competitiveness over copper and copper alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cryogenic temperature (CT) SPD is developed to conquer the aforementioned limitation. Yu et al [14] found the ultimate tensile stress of Al/Ti/Al laminate sheets processed by cryogenic roll bonding was 36.7% higher than that by room-temperature roll bonding. By the way, edge cracks also appear in the latter, but the former is in good shape.…”
Section: Introductionmentioning
confidence: 99%